2021
DOI: 10.1007/s10126-020-10015-2
|View full text |Cite
|
Sign up to set email alerts
|

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia

Abstract: Sexual dimorphism is common across the animal kingdom. Knowledge of the mechanisms of sexual size dimorphism is limited although it is important in biology and aquaculture. Tilapia is the common name for ~100 species of cichlid fish. Some are important aquaculture species and males outgrow females. To gain novel insights into the mechanisms underlying sexual size dimorphism, we analyzed the differences of brain transcriptomes between males and females in Mozambique tilapia and studied the function of the pro-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…When fishes reach sexual maturity, the brain’s differentiation in both sexes is completed due to exposure to different sex steroid hormones. Previous studies have reported Pomc as a candidate gene for SSD in tilapia ( Wan et al, 2021 ). Its high expression in the female tilapia brain has been associated with the slow growth of the fish ( Wan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…When fishes reach sexual maturity, the brain’s differentiation in both sexes is completed due to exposure to different sex steroid hormones. Previous studies have reported Pomc as a candidate gene for SSD in tilapia ( Wan et al, 2021 ). Its high expression in the female tilapia brain has been associated with the slow growth of the fish ( Wan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To knockout one target gene/sequence, it is essential that several sgRNAs are designed to ensure high successful rate of knockout. 60 After getting Cas9 and sgRNAs, they are mixed (e.g. 250 ng/µl Cas9 and 200 ng/µl of sgRNA in RNase free water) in a final volume of 5 µl.…”
Section: Technolog Ie S Of G Enome Ed Itingmentioning
confidence: 99%
“…250 ng/µl Cas9 and 200 ng/µl of sgRNA in RNase free water) in a final volume of 5 µl. 60 One nanoliter of the mixture is injected into fertilised eggs at the one-cell stage. Usually, one-cell fertilised eggs are obtained with artificial insemination.…”
Section: Technolog Ie S Of G Enome Ed Itingmentioning
confidence: 99%
See 2 more Smart Citations